The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/0004-282x20160181
|View full text |Cite
|
Sign up to set email alerts
|

MacArthur Competence Assessment Tool for Treatment in Alzheimer disease: cross-cultural adaptation

Abstract: Objective: We adapted the MacArthur Competence Assessment Tool for Treatment (MacCAT-T) to Brazilian Portuguese, pilot testing it on mild and moderate patients with Alzheimer's disease (AD). Methods: The cross-cultural process required six steps. Sixty-six patients with AD were assessed for competence to consent to treatment, global cognition, working memory, awareness of disease, functionality, depressive symptoms and dementia severity. Results: The items had semantic, idiomatic, conceptual and experiential e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 24 publications
1
18
1
Order By: Relevance
“…The MacArthur Competence Tool for Treatment (MacCAT-T; adapted to Brazilian Portuguese; Santos et al, 2017) was used to assess competence to consent to treatment (Grisso et al, 1997). This scale permits to explore four different abilities: understanding, appreciation, reasoning and expression.…”
Section: Methodsmentioning
confidence: 99%
“…The MacArthur Competence Tool for Treatment (MacCAT-T; adapted to Brazilian Portuguese; Santos et al, 2017) was used to assess competence to consent to treatment (Grisso et al, 1997). This scale permits to explore four different abilities: understanding, appreciation, reasoning and expression.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, studies suggested a relationship between decision-making capacity and awareness of disease 11–13. People with Alzheimer dementia (PwAD) who were aware of their overall cognitive function and diagnosis were more likely to be judged competent in decision-making capacity 14. Gambina et al15 found that people with partially preserved decision-making capacity were aware of their memory deficit.…”
mentioning
confidence: 99%
“…14 Gambina et al 15 found that people with partially preserved decision-making capacity were aware of their memory deficit. In addition, Santos et al 14 reported that awareness of disease was only related to the ability to express a choice in decisionmaking. Moreover, unawareness among people with moderate dementia has been related to significant impairment in understanding, appreciating, and reasoning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most concerning aspect of the study is that the clinical team responsible for these patients had identified only approximately one quarter as being unable to consente 1 . In this issue of the Arquivos de Neuropsiquiatria, Santos et al 2 present their adaptation of the MacArthur Competence Assessment Tool (MacCAT-T) 3 to Brazilian Portuguese, testing it in patients with Alzheimer's disease (AD). The MacCAT-T isMacCAT-T) is a tool focused on clinical assessment, successfully applied in patients with dementia, mild cognitive impairment, and psychiatric conditions.…”
mentioning
confidence: 99%